Soil and rock - Materials, American Society for Testing and. ([S.l.] : ASTM, 2009)
Geotechnical and geoenvironmental standards cover soil testing, including compaction, sampling, field investigation, cyclic and dynamic properties, soil texture, plasticity, density characteristics, hydrological properties, hydraulic barriers, and rock for erosion control.